Między Północą a Południem. Osadnictwo schyłkowopaleolityczne i mezolityczne w dolnym biegu Warty - Jankowska, Dobrochna; Rozbiegalski, Piotr (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
The paper outlines the preliminary results of the project ‘Final Palaeolithic and Mesolithic settlement in the area of the lower reaches of the Warta River’. No traces of such early settlement had been hitherto recognised in the investigated area. The project yielded 1500 sites with flint artefacts in the area. Over 80 sites have been classified as the Final Palaeolithic and/or Mesolithic. The distribution of the sites together with the environmental conditions and the analysis of the artefacts allowed for some hypotheses to be verified in further stages of the project.
Between North and South. Final Palaeolithic and Mesolithic settlement in the area of the lower reaches of the Warta river